Simple, green and one pot new strategy for synthesis of the phthalimide derivatives. (22nd June 2022) - Gholami, Fatemeh; Moazzam, Ali; Hosseini, Samanesadat; Larijani, Bagher; Adib, Mehdi; Mahdavi, Mohammad
Graphical abstract: Abstract: A novel, simple, green, one pot and practical synthetic method is described for the preparation of phthalimide derivatives through a condensation reaction between of 2-formylbenzoic acid and aniline in the presence of Et3 N as base and S8 (Octasulfur) as oxidant in solvent free condition. This one-pot protocol provides these valuable desired compounds under mild conditions with excellent efficiency by using simple available starting materials.